Physical Exercise under Positive Psychology Improves the Psychological Sub-health State of International Trade Workers - Yongjiang Ding; Junfeng Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Scientific sports can strengthen the body and foster the growth of physical excellence. The body can develop normally and provide a solid material foundation for the development of mental health through participation in sports. This study aims to determine how physical activity can enhance the mental health of international trade workers. The Physical Exercise Rating Scale, the Adolescent Sub-health Multidimensional Assessment Questionnaire, and the International Trade Worker Coping Scale are utilized to select and measure international trade workers in the athletics dance exercise group and the passive and inactive group. Covariance analysis examines the differences between groups, while the structural equation model and the Sobel test are employed to analyze the mediation effect. The differences in scores of problem orientation, emotion orientation, and avoidance orientation between the sports dance group and the passive and inactive group are statistically significant (P0.05), as are the differences in scores of psychological sub-health emotional problems and social adjustment issues. In addition, the problem orientation dimension of coping styles is statistically significant for "whether to participate in sports dance" The problem orientation dimension of managing style functions as a partial mediator between "whether or not to participate in sports dance exercise" and the sub-health psychological, and emotional problems dimension.